Propiedades mecánicas de un compuesto polimérico hecho de polietileno de baja densidad reciclado y reforzado con fibras de madera natural (2016)
The thermoplastic polymers generated worldwide and their great environmental impact, are increasing uncontrollably. This has made it necessary to take advantage of them using recycling processes, which allow the manufacture of new products, preventing these polymers from ending up in landfills.  Recently the materials are being used as raw materials in the manufacture of wood and plastic compounds (WPCs).  With the goal of recovering these waste materials (wood sawdust and polymer), in this study a material of combined wood and polymer was created, to evaluate its mechanical properties, using LDPE as a matrix, mixed with natural wood fibers, added as reinforcement. This compound material was formed under heat via the process of extrusion, varying the proportions of polymer mix: sawdust.  For the obtained materials, the mechanical properties of traction resistance and bending resistance were measured, the maximum traction resistance was obtained by the compound which contained 20% wood fibers, but in excess of the indicated percentage the resistance began to decline.  The morphology was analyzed via MEB, it is clear that despite the increase in resistance, the bond between matrix and reinforcement is not optimal.  It was observed that the resistance of the wood and polymer compound material increased in relation to the resistance of the polymer.  With the obtained properties this material could be used in the manufacture of components such        as pallets, platforms for covering gardens, pool surroundings, garden fences.